The Effect of Clomid (Clomiphene Citrate) on Chickens: II. Histo-Physiological Study - AL-KHAZRAJI, A. K.; SHANAWANY, M. M.; HAMED, O. M. (The Libyan Journal of Agriculture, 2023)
A group of 16 Single Comb White Leghorn-type pullets were force-fed 2 mg of Clomid2/bird/day. Overstimulation of the ovarian and oviductal activities was observed. The germinal epithelia exhibited high cuboidal cells and the cortices contained numerous developing follicles.In the oviduct, at the funnel magnum junction, the cilia became crowed and the secretory cells were hyperplastic with cytoplasms full of secretions. Sections taken from the magnum showed that the epithelium mucus cells were ciliated and loaded with secretions. The arrangement of these cells was irregular giving the entire epithelia a pseudostratified-like pattern. The glandular cells were hypertrophic and hyperchromatic. The shell gland exhibited epithelium of highly pseudostratified columnar cells. Some of these cells were hyperplastic; the others were hypertrophic. The cell’s cytoplasms were full of secretions.